2018
DOI: 10.1002/hbm.24402
|View full text |Cite
|
Sign up to set email alerts
|

Resting state functional connectivity of networks associated with reward and habit in anorexia nervosa

Abstract: Neurobiological disturbances associated with reward and/or habit learning are theorized to maintain symptoms of anorexia nervosa (AN). Although research has investigated responses in brain regions associated with reward and habit to disorder-specific cues (e.g., food) and presumed rewards (e.g., money), little is known about the functional organization of the circuits underlying these constructs independent of stimulus. This study aimed to provide initial data on the synchrony of networks associated with rewar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 49 publications
(119 reference statements)
6
39
0
Order By: Relevance
“…Subtypes effects have not been systematically assessed in prior research. Some studies have not reported subtype analyses (Biezonski et al, ; Favaro et al, ; Phillipou et al, ) and other studies only included AN‐R (Haynos et al, ). One study had unbalanced numbers in each subtype group which limited between‐group comparisons (Boehm et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subtypes effects have not been systematically assessed in prior research. Some studies have not reported subtype analyses (Biezonski et al, ; Favaro et al, ; Phillipou et al, ) and other studies only included AN‐R (Haynos et al, ). One study had unbalanced numbers in each subtype group which limited between‐group comparisons (Boehm et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The direction of effect differs across studies. Our patient sample was unmedicated and included individuals with both AN subtypes, whereas the study by Haynos et al () permitted psychotropic medications and studied individuals with AN‐R only. As frontal activation has been shown to change with psychotropics (Posner et al, ), medication status may influence frontostriatal circuit connectivity results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As abovementioned, parietal cortex is severely involved. Functional neuroimaging studies reported its alteration (Kojima et al, 2005;Van Kuyck et al, 2009) specifying that parietal activity at rest is treatment sensitive, since it increases after treatment (Delvenne et al, 1995;Kojima et al, 2005 (Haynos et al, 2019).…”
Section: Frontos Triatal Sys Temmentioning
confidence: 99%